KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI DUSUN MUMBANG, DESA MONTONG GAMANG, KECAMATAN KOPANG, KABUPATEN LOMBOK TENGAH - Elsa Noviasari; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Montong Gamang is a village in Kopang District, Central Lombok Regency. The study was conducted using observational methods. Based on the study, it was found that yard plants in Mumbang Hamlet, Montong Gamang Village, Kopang District, Central Lombok Regency had an H’=1.97, indicating moderate diversity and high evenness, which reflects a relatively stable community condition.